Informática na Educação de jovens e adultos: Análise de um Programa de Intervenção a favor da inclusão social e digital - Amparo, Matheus Augusto Mendes [UNESP] (2015)
The present study is linked to the research Practices and Formation Processes in Education a Post-graduation studies program in Education at Faculdade de Ciências e Tecnologias- UNESP, Presidente Prudente/SP Campus and it has as its study object the Teaching Young and Adult Education (EJA) method and the importance of the social and digital inclusion for learners so they can exercise their citizenship in the current society. Therefore, the problem of the research is: how to develop an intervention program in computer science focused on Youth and Adult Education having in mind the social and digital inclusion of learners? To do this, the general objective of this research was to develop and analyze a computer intervention program in Young and Adult Education and its possible contributions to the process of social and digital inclusion of these students. This paper had as theoretical contribution studies related to the education of Young people and Adults, Information Society and Knowledge, Social and Digital Inclusion and Technologies in Education. The survey took place between the years 2013 and 2014 in a room of EJA in a city school in Presidente Prudente/SP. It was characterized as a qualitative approach and it has used as its technical procedure the interventional research. For the data collection it was used the interview, the form and notes, the records were made by means of filling out diaries and pictures and the data analysis was performed by content analysis...